Internalizing Character Education (CE) into English Language Teaching: Teachers’ Perspectives - Anggun And Joy Nenohai; Listyani Listyani; Joseph Ernest Mambu (Kelola: Jurnal Manajemen Pendidikan, 2021)
Character Education (CE) is an extensive issue in Indonesia’s education field, especially after 2013 Curriculum was introduced, but how English as a Foreign Language (EFL) teachers critically perceive it in the English Language Teaching (ELT) setting has become very urgent. Therefore, the purpose of this study is to investigate EFL teachers’ insights on undertaking the values of CE within the teaching and learning process. Two in-service teachers of a private Christian-based junior high school in Salatiga were interviewed. The classroom observations were also conducted to investigate the implementation and practicality of CE in EFL classrooms. The data collection was analyzed in light of the theoretical framework related to CE by Aristotle (1984, as cited in Wren, 2014), Dewey (1996, as cited in Liu, 2014), Pessoa and de Urzȇda Freitas (2012), Celce-Murcia (2007), and Mambu (2015). The results showed that the values of CE in the 2013 Curriculum were internalized differently based on the inclusivity of their perspectives. Second, the teachers justified that the values of CE that were selectively involved in the teaching and learning activities should be relevant to the context. Next, the practice of CE was attempted to promote critical thinking. Last, teachers are expected to create a better implementation of the values of CE related to the students' real contexts.